2008
DOI: 10.1179/174329008x284868
|View full text |Cite
|
Sign up to set email alerts
|

Iron–manganese: new class of metallic degradable biomaterials prepared by powder metallurgy

Abstract: An Fe-35 wt-%Mn alloy, aimed to be used as a metallic degradable biomaterial for stent applications, was prepared via a powder metallurgy route. The effects of processing conditions on the microstructure, mechanical properties, magnetic susceptibility and corrosion behaviour were investigated and the results were compared to those of the SS316L alloy, a gold standard for stent applications. The Fe35Mn alloy was found to be essentially austenitic with fine MnO particles aligned along the rolling direction. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
173
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(175 citation statements)
references
References 32 publications
1
173
0
1
Order By: Relevance
“…Therefore, our research group has developed an iron-manganese alloy through a powder metallurgical process. It was found that 35% manganese, here after denoted simply as alloy, showed comparable mechanical properties to that of the stainless steel [5].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, our research group has developed an iron-manganese alloy through a powder metallurgical process. It was found that 35% manganese, here after denoted simply as alloy, showed comparable mechanical properties to that of the stainless steel [5].…”
Section: Introductionmentioning
confidence: 98%
“…Several materials have been reported as potential degradable metallic materials (DMMs) for cardiovascular stent application including pure iron [4], Fe-35Mn alloy [5], magnesium alloy [6][7], and others. For cardiovascular stent application, iron based materials present suitable ductility compared to that of magnesium-based materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among Mg-based alloys have been studied, include MgAl- (Heublein, 2003, Witte, 2005, Xin, 2007), MgRE-(Di Mario, 2004, Peeters, 2005, Witte, 2005, Waksman, 2006, Hänzi, 2009) and MgCa- (Zhang, 2008, Li, 2008 based alloys. Meanwhile, for Fe-based alloys, pure iron (Peuster, 2001, Peuster, 2006 and FeMn alloys (Hermawan, 2008, Schinhammer, 2009) have been investigated mainly for cardiovascular applications. Among the most advanced studies on biodegradable metals is the development of stents.…”
Section: Biodegradable Metalsmentioning
confidence: 99%
“…The Mg-based alloys include MgAl-, MgRE (rare earth)- (Witte, 2005), and MgCa-(Li, 2008) based alloys. Meanwhile, the Fe-based alloys include pure iron (Peuster, 2001) and Fe-Mn alloys (Hermawan, 2008). …”
mentioning
confidence: 99%